The Influence of Government Fleet Maintenance Service on Client Satisfaction: A Case of Tanzania Electrical and Mechanical Services Agency - Hancha, Husein Abubakari; Muya, Francis (Journal of Industrial Engineering & Management Research, 2025)
This study evaluates how the quality of government fleet maintenance services influence client satisfaction at TEMESA in Tanzania. It focused on five main service quality dimensions: tangibility, reliability, responsiveness, assurance, and empathy. The research followed a positivist philosophy and a deductive approach, using a cross-sectional design to collect quantitative data. A sample of 201 employees from NHIF, TANESCO, and TRA in Dar es Salaam was selected through simple random sampling. Data were gathered using structured questionnaires and analysed using SPSS, employing descriptive statistics such as means and standard deviations, as well as inferential analyses including correlation and multiple regression. The findings revealed mixed results. Tangibility and assurance showed no significant influence on client satisfaction, indicating they did not play a major role in improving fleet maintenance service quality. On the other hand, reliability and responsiveness had significant positive influence, meaning that when services were dependable and promptly delivered, clients were more satisfied. Interestingly, empathy had a significant but negative influence, suggesting that too much personal concern or emotional involvement from service providers could reduce satisfaction. The study concludes that improving reliability and responsiveness is crucial for enhancing client satisfaction in government fleet maintenance. However, managing empathy appropriately is necessary to prevent dissatisfaction. It recommends that TEMESA strengthen systems to ensure timely and reliable services and train staff to maintain professionalism while interacting with clients. The study provides useful guidance for public institutions to improve service quality and enhance customer satisfaction.